2007
DOI: 10.1080/10623320701678268
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome of Angiopoietin 1–Activated Human Umbilical Vein Endothelial Cells

Abstract: Angiopoietin 1 (Ang-1) is the main ligand for endothelial cell-specific tyrosine kinase (Tie-2) receptors and it promotes migration and proliferation and inhibits apoptosis and vascular leakage. The exact mechanisms through which the Ang-1 exerts these effects remain unclear. The authors exposed human umbilical vein endothelial cells (HUVECs) to Ang-1 (300 ng/mL) for 4 h and conducted gene expression profiling using oligonucleotide microarrays. Real-time polymerase chain reaction (PCR) was also conducted to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…We have recently reported that mTOR and its downstream effector, p70S6 kinase, are activated downstream from Tie-2 receptors in HUVECs and that mTOR participates in Ang-1-induced alterations in the HUVEC transcriptome. 4 Very little is known about interactions between Egr-1 and the mTOR network, although it has been demonstrated that induction of Egr-1 expression is mediated, in part, through the mTOR/P70S6 kinase pathway during skeletal myoblast differentiation. 18 We also confirm here that the p38 MAPK pathway inhibits Egr-1 transcription and that this effect is mediated through a negative influence on Erk1/2 pathway activation.…”
Section: Abdel-malak Et Al Egr-1 In Angiopoietin-1 Signaling 213mentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported that mTOR and its downstream effector, p70S6 kinase, are activated downstream from Tie-2 receptors in HUVECs and that mTOR participates in Ang-1-induced alterations in the HUVEC transcriptome. 4 Very little is known about interactions between Egr-1 and the mTOR network, although it has been demonstrated that induction of Egr-1 expression is mediated, in part, through the mTOR/P70S6 kinase pathway during skeletal myoblast differentiation. 18 We also confirm here that the p38 MAPK pathway inhibits Egr-1 transcription and that this effect is mediated through a negative influence on Erk1/2 pathway activation.…”
Section: Abdel-malak Et Al Egr-1 In Angiopoietin-1 Signaling 213mentioning
confidence: 99%
“…These genes are known targets of the Ang-1/Tie-2 receptor pathway and Egr-1-mediated transcription. 4,5 Genes were detected 24 hours after transfection of HUVECs with siRNA oligonucleotides or DNAzymes. Results were analyzed using the comparative threshold cycle (C T ), as previously described.…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Exposure to Ang-1 resulted in induction of 86 genes that are involved in EC proliferation, differentiation, migration, and survival. In addition, Ang-1 elicited a significant decline in the expression of 49 genes, most of which are involved in cell-cycle arrest, apoptosis, and suppression of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…38 VEGF-C released by platelets, monocytes, macrophages, and BEC, 39 also regulates BEC proliferation, vascular permeability, 40 capillary formation, 41 inflammatory-activation, 42 and leukocyte binding to BEC. 37 VEGF-C and VEGF-D also play dominant roles in BEC and LEC survival, proliferation, migration, capillary formation in vivo and in vitro; 43 their effects in inflammation are less well characterized.…”
mentioning
confidence: 99%